Angelman Syndrome Due to a Termination Codon Mutation of the UBE3A Gene. (March 2013) - Al-Maawali, Almundher; Machado, Jerry; Fang, Ping; Dupuis, Lucie; Faghfoury, Hannaneh; Mendoza-Londono, Roberto
Angelman syndrome is a neurodevelopmental disorder characterized by global developmental delay, mental retardation, seizures, microcephaly, and severe speech delay. It may be caused by deletion of chromosome region 15q11.2 of the maternally inherited chromosome, mutations in the UBE3A gene, uniparental disomy, or imprinting defects. Most patients with this diagnosis have a severe phenotype, and a few have a mild form of the disease. We report a patient with a novel mutation in the UBE3A gene that consists of a deletion of the termination codon (c.2556-*+6del GTAAAACAAA) and results in an elongated protein E3 ubiquitin–protein ligase. Our patient has a mild phenotype compared with other patients in general and specifically to patients with UBE3A mutations. He has mild developmental delay, moderate speech delay, and no seizures. Recognition of this genotype–phenotype correlation will allow better genetic counseling to other patients with similar stop codon mutations.